Interstellar polarisation towards a region around the Bok globule B5 - Krayani, H. A.; Il'in, V. B.
We report the results of our spectroscopic and polarimetric observations of 2° x 2° field around the globule Barnard 5 (B5) belonging to the Perseus cloud complex at the distance d ≈ 300pc. Using these data, two-dimensional spectral classification was made for about 45 stars. Multi-band polarimetry of about 20 of these stars allowed us to find the parameters (Pmax, λmax) of interstellar polarization. Using the Gaia parallaxes and data from the recent photometric surveys, we estimate the interstellar extinction AV towards the stars. Our analysis of à variations of the parameters AV , Pmax, λmax in the sky plane and with the distance allows us to conclude that in the considered field (excluding the halo of B5) the main contribution to the extinction and polarization is provided by an extension of the Taurus cloud complex (TMC) at d ≈ 150 pc, and that the derived values of the parameters indicate that the angle between the line of sight and the magnetic field direction in this part of TMC significantly differs from 90o.
Keywords: Astrophysics